An Assessment of the Distinction between Ishārī Tafsīr and Taṣawwufī Tafsīr - SAK, Hasan İslam (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2026)
This study examines ishārī tafsīr, a contested concept in the tafsīr literature, with regard to its meaning and content. It analyzes the effects of the differing usages of the constituent term ishārah across various Islamic disciplines on the definition of ishārī tafsīr. The study has established that conflating these different usages under a single compound term has resulted in conceptual ambiguity regarding the scope and nature of ishārī tafsīr. To resolve this ambiguity, interpretations commonly classified as ishārī tafsīr are examined and differentiated according to their defining characteristics, and a terminological and definitional proposal is put forward. Foregrounding the juridical usage of ishārah, the study argues that interpretations deriving indirect meanings from the lexical or semantic indications of the Qurʾānic text, whose connection with the text can be established, should properly be designated as ishārī tafsīr. By contrast, Sufi explanations distinguished by their source of knowledge, content, terminology, and pedagogical orientation are more appropriately classified as taṣawwufī tafsīr. The study further notes that some Sufi interpretations that establish a clear link with the text may be treated as an intermediate category designated as “taṣawwufī–ishārī tafsīr.” Methodologically, data gathered through a literature review were analyzed by means of content analysis; the topic was addressed primarily within a theoretical framework and supported by examples. It has been concluded that the proposed distinction will contribute to a more consistent and sound evaluation of Qurʾānic interpretations.